PELESTARIAN TAPIS CORAK INUH MELALUI PEMBIAYAAN FINTECH DI KABUPATEN LAMPUNG SELATAN - Maulidiana, Lina; Dewi , Ade Sandra; Pujiati , Ani; Setia, Wahyu Darma; Pramudita, Rika (LPPM Universitas Bina Bangsa, 2024)
The community service activity titled